TOP3A amplification and ATRX inactivation are mutually exclusive events in pediatric osteosarcomas using ALT. Issue 10 (3rd August 2022) - de Nonneville, Alexandre; Salas, Sébastien; Bertucci, François; Sobinoff, Alexander P; Adélaïde, José; Guille, Arnaud; Finetti, Pascal; Noble, Jane R; Churikov, Dimitri; Chaffanet, Max; Lavit, Elise; Pickett, Hilda A; et al.
Abstract: In some types of cancer, telomere length is maintained by the alternative lengthening of telomeres (ALT) mechanism. In many ALT cancers, the α‐thalassemia/mental retardation syndrome X‐linked ( ATRX ) gene is mutated leading to the conclusion that the ATRX complex represses ALT. Here, we report that most high‐grade pediatric osteosarcomas maintain their telomeres by ALT, and that the majority of these ALT tumors are ATRX wild‐type (wt) and instead carry an amplified 17p11.2 chromosomal region containing TOP3A . We found that TOP3A was overexpressed in the ALT‐positive ATRX‐wt tumors consistent with its amplification. We demonstrated the functional significance of these results by showing that TOP3A overexpression in ALT cancer cells countered ATRX‐mediated ALT inhibition and that TOP3A knockdown disrupted the ALT phenotype in ATRX‐wt cells. Moreover, we report that TOP3A is required for proper BLM localization and promotes ALT DNA synthesis in ALT cell lines. Collectively, our results identify TOP3A as a major ALT player and potential therapeutic target. Synopsis: There is an urgent need to treat pediatric osteosarcomas that present high frequency of alternative lengthening of telomeres (ALT). This study identifies TOP3A amplification as mutually exclusive with ATRX inactivation, promoting ALT and TOP3A action at telomeres as a novel therapeutic target. 17p11 amplification and ATRX mutation are exclusive genomic events in ALT high‐grade pediatric osteosarcomas. TOP3A overexpression is a feature of ATRX‐wt ALT osteosarcomas. Over‐expression of TOP3A correlates with the presence of ATRX in ATRX‐wt ALT cell lines. TOP3A is required for proper BLM localization in ALT osteosarcoma cell lines and promotes ALT‐mediated telomeric DNA synthesis. Abstract : There is an urgent need to treat pediatric osteosarcomas that present high frequency of alternative lengthening of telomeres (ALT). This study identifies TOP3A amplification as mutually exclusive with ATRX inactivation, promoting ALT and TOP3A action at telomeres as a novel therapeutic target.